Association between digital technology use and social capital among older adults: A systematic review - Giulia Grotto; Alessandra Buja (Digital Health)
Background Social capital refers to the valuable resources that individuals can access through their social networks, which are often established within family ties, professional affiliations, community organizations, and neighborhoods. Evidence suggests that there is a positive association between social capital and well-being, health status, and sociability. Research has found a positive association between digital technology use and social capital, though limited attention has been paid to older adults. This systematic review aims to evaluate the association between digital technology use and social capital among older adults. Methods Five scientific electronic databases were searched for eligible studies in October 2024. The search strategies were developed by combining the keywords of the three main axes of the research (“older adults,” “digital technology,” and “social capital”) and respective synonyms using Boolean operators. The review protocol was developed in advance and registered in PROSPERO (CRD42024614622). Results The research strategy returned a total of 1229 citations from electronic databases, 20 of which met the exclusion and inclusion criteria. All the included studies had a cross-sectional design, and the samples of the included studies ranged from 118 to 9642 individuals. All the included studies found a positive association between digital technology and social capital among older adults. Conclusions Digital technology can offer opportunities to maintain or increase social capital, that typically tends to reduce with age. Since social capital positively impacts health and well-being, the importance of enabling older adults to use digital technologies must be considered when designing and implementing health behavior intervention programs.